Analisis dan Perbaikan Usability Situs Halo FILKOM menggunakan Metode Design Thinking dan System Usability Scale - Ilham Hananto Wibisono; Satrio Hadi Wijoyo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Halo Filkom website is here to help students who need information related to services, technical support, question, and submitting complaints to all services at FILKOM UB by utilizing the e-ticketing system. The researcher found that although the Halo Filkom website was feasible to use, because it was relatively new, several complaints from students of the Faculty of Computer Science were found, such as the design being too rigid, tickets closing too quickly, or the ticketing system being confusing for new users. For this reason, it is necessary to evaluate the Halo Filkom site so that it will be better in the future. The method used to evaluate and improve the Halo Filkom website is the design thinking method. The reason researchers use the design thinking method is because this method can help researchers explore user needs more deeply. With qualitative research methods like interviews, compared to quantitative like surveys. With the empathize stage in this method, it can involve respondents to participate in brainstorming related to complaints and ideas in the future development of the Halo Filkom website. Data collection for the evaluation was carried out using the interview method consisting of students and stakeholders. In addition, an evaluation using the System Usability Scale (SUS) was also carried out with the aim of assessing the usability of the website before redesigning it. It was found that the SUS website scores 54.5 points. After making design improvements such as making tutorials for new users, improving pages so that they are not rigid, and other improvements. After the redesign, the SUS test was carried out again and it was found that the score increased to 91.5 points. It can be concluded that the process of evaluating and improving the website using the design thinking method succeeded in increasing the SUS score by 37 points or 67.88%.